2012
DOI: 10.1371/journal.pone.0048895
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Hippocampal Volume in Healthy Young ApoE4 Carriers: An MRI Study

Abstract: The E4 allele of the ApoE gene has consistently been shown to be related to an increased risk of Alzheimer's disease (AD). The E4 allele is also associated with functional and structural grey matter (GM) changes in healthy young, middle-aged and older subjects. Here, we assess volumes of deep grey matter structures of 22 healthy younger ApoE4 carriers and 22 non-carriers (20–38 years). Volumes of the nucleus accumbens, amygdala, caudate nucleus, hippocampus, pallidum, putamen, thalamus and brain stem were calc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
103
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 177 publications
(116 citation statements)
references
References 84 publications
8
103
5
Order By: Relevance
“…Nominally significant associations of an APOE risk variant with HV (P=0.0054) and a CD33 variant with ICV (P=0.0058) were observed. Since the mid 1990's (Supplementary Table 5) some studies have described significant associations between the APOE-ε4 allele and smaller HV (den Heijer, et al, 2002, Lehtovirta, et al, 1995, Lehtovirta, et al, 1996, Lind, et al, 2006, Liu, et al, 2014, Lu, et al, 2011, Morra, et al, 2009, O'Dwyer, et al, 2012, Plassman, et al, 1997, however other studies did not find such an association (Ferencz, et al, 2013, Reiman, et al, 1998, Schmidt, et al, 1996. Using the largest sample size to date (N=11,550), as previously reported by our group, our findings are supportive of an association of the APOE-ε4 locus with smaller HV .…”
Section: Discussionsupporting
confidence: 85%
“…Nominally significant associations of an APOE risk variant with HV (P=0.0054) and a CD33 variant with ICV (P=0.0058) were observed. Since the mid 1990's (Supplementary Table 5) some studies have described significant associations between the APOE-ε4 allele and smaller HV (den Heijer, et al, 2002, Lehtovirta, et al, 1995, Lehtovirta, et al, 1996, Lind, et al, 2006, Liu, et al, 2014, Lu, et al, 2011, Morra, et al, 2009, O'Dwyer, et al, 2012, Plassman, et al, 1997, however other studies did not find such an association (Ferencz, et al, 2013, Reiman, et al, 1998, Schmidt, et al, 1996. Using the largest sample size to date (N=11,550), as previously reported by our group, our findings are supportive of an association of the APOE-ε4 locus with smaller HV .…”
Section: Discussionsupporting
confidence: 85%
“…31 MCI patients were further dichotomized as APOE "4 carriers (APOE "3/"4 and APOE "4/"4) or non-carriers (APOE "3/"3).…”
Section: Genotypingmentioning
confidence: 99%
“…Thus, several studies have reported a significant atrophy (or cortical thinning) in APOE4 carriers compared to non carriers, most often in brain regions most susceptible to AD, i.e. medial temporal structures (hippocampus, entorhinal cortex, etc;Plassman et al, 1997;Tohgi et al, 1997;Lemaître et al, 2005;Lind et al, 2006;Wishart et al, 2006;Burggren et al, 2008;Honea et al, 2009;Suthana et al, 2010;O'Dwyer et al, 2012). Other regions are also reported such as the lateral temporal and prefrontal cortex (Wishart et al, 2006) or parietal areas (Honea et al, 2009).…”
Section: Apoe4 and Structural Mri / Atrophymentioning
confidence: 99%